RARE-21. A RARE CASE OF PEDIATRIC SPINDLE CELL ONCOCYTOMA WITH EML4-ALK FUSION. (1st June 2021) - Michaiel, George; Hawes, Debra; Guzman, Samuel; Margol, Ashley; Biegel, Jaclyn; Ji, Jianling
Abstract: A 12 year-old male presented with a 2-month history of intermittent headaches, nausea, and vomiting. Magnetic resonance imaging (MRI) of the brain revealed a 2.2 x 3.5 x 2.6 cm lobulated, sellar/suprasellar mass, mildly T1/T2 hyperintense, with mild homogeneous enhancement and diffusion restriction. He underwent transsphenoidal and right craniotomies for gross total resection of the mass. Pathology demonstrated a hypercellular neoplasm with spindled to ovoid tumor cells arranged in fascicles and tight whirls, consistent with a spindle cell oncocytoma. OncoKids, a DNA- and RNA-based next generation sequencing panel, demonstrated an in-frame EML4 exon 2-ALK exon 19 fusion with a total of 179, 872 supporting reads. The EML4-ALK fusion gene is predicted to encode a chimeric tyrosine kinase that facilitates multimerization and autophosphorylation of ALK, and activates its downstream targets, such as RAS/ERK, PI3K/AKT, and JAK/STAT pathways. This fusion is found in approximately 5% of patients with non-small cell lung cancer, a subset of inflammatory myofibroblastic tumors, as well as single cases of pulmonary atypical carcinoid, cholangiocarcinoma, and high-grade glioma. However, it has not been previously described in oncocytoma. Chromosomal microarray analysis demonstrated two interstitial non-contiguous deletions in 2p, and an interstitial deletion in 18q that does not include any known cancer-related genes. The deleted segment in 2p23.3p23.2 includes DNMT3A, which mediates DNA methylation and functions in modification of gene expression. DNMT3A mutations are frequent in hematological malignancies, however their role in oncocytoma is currently unknown. The proximal breakpoint of the deletion in 2p23.3p23.2 is in close proximity to but does not reside within ALK. Spindle cell oncocytoma is rarely reported in the pediatric population, with only one case described in the literature. This is the first case report of an oncocytoma with an EML4-ALK fusion. Additional studies are warranted to confirm its functional effect.